(untitled) (Conference Zone, 2021)
The article describes the problems of mental health, one of the most pressing issues of today, and its foundations, mental health problems and solutions that plague the population. Reproductive health declines, which are reflected in a sharp decline in births, divorces, and an increase in the number of incomplete and unemployed families.